Developing community-based urine sampling methods to deploy biomarker technology for the assessment of dietary exposure. Issue 17 (11th December 2020) - Lloyd, Amanda J; Wilson, Thomas; Willis, Naomi D; Lyons, Laura; Phillips, Helen; Janssen, Hayley G; Stiegler, Martina; Xie, Long; Tailliart, Kathleen; Beckmann, Manfred; Stevenson, Leo; Mathers, John C; et al.
Abstract: Objective: Obtaining objective, dietary exposure information from individuals is challenging because of the complexity of food consumption patterns and the limitations of self-reporting tools (e.g., FFQ and diet diaries). This hinders research efforts to associate intakes of specific foods or eating patterns with population health outcomes. Design: Dietary exposure can be assessed by the measurement of food-derived chemicals in urine samples. We aimed to develop methodologies for urine collection that minimised impact on the day-to-day activities of participants but also yielded samples that were data-rich in terms of targeted biomarker measurements. Setting: Urine collection methodologies were developed within home settings. Participants: Different cohorts of free-living volunteers. Results: Home collection of urine samples using vacuum transfer technology was deemed highly acceptable by volunteers. Statistical analysis of both metabolome and selected dietary exposure biomarkers in spot urine collected and stored using this method showed that they were compositionally similar to urine collected using a standard method with immediate sample freezing. Even without chemical preservatives, samples can be stored under different temperature regimes without any significant impact on the overall urine composition or concentration of forty-six exemplar dietary exposure biomarkers. Importantly, the samples could be posted directly to analytical facilities, without the need for refrigerated transport and involvement of clinical professionals. Conclusions: This urine sampling methodology appears to be suitable for routine use and may provide a scalable, cost-effective means to collect urine samples and to assess diet in epidemiological studies.